Pengaruh temperatur pelat landasan selama hot gas welding terhadap karakteristik kekuatan lasan lembaran HDPE - Agus Setiawan; Kris Witono; Riswan E.W. Susanto (Politeknik Negeri Lhokseumawe, 2020)
Plastic material failures such as fractures or can be repaired by joining. In the industrial world, the joining of two or more plastic parts can be done with plastic welding technology, one of the methods of plastic welding is hot-gas welding (HGW). HGW is a welding process for plastic materials, but it is known that plastic materials have poor heat conductivity. The aim of this research is to improve the quality of plastic material joints, in this case HDPE sheets, and effect of the base plate temperature and hot-gas temperature on the strength and impact, as well as the interaction effect of the base plate temperature and hot-gas temperature on tensile and hit strength. The method used in data collection is data processing method using factorial DOE. The temperature variation of the base plate during the welding process (30° C, 70° C, 110° C and 150° C), as well as the temperature of the hot air flow from the hot-gun (250° C, 300° C, and 350° C). To obtain the data, it was carried out by tensile and hit tests using standard specimens, respectively ASTM D 638-03 and ASTM D 6110. From the research results, it was found that the ground temperature and hot air flow temperature of the hot gun during the hot gas welding process had an effect on the tensile strength and hit HDPE weld joints. Optimization of tensile strength and hitting strength, respectively 18.78 MPa and 0.018567 J/mm2 (85.65% and 89.74% of the strength of HDPE without joints), these values are obtained from the combination of an anvil plate temperature of 150° C and flow hot air hot gan 250° C.